Increased plasma levels of miR-124-3p, miR-125b-5p and miR-192-5p are associated with outcomes in acute ischaemic stroke patients receiving thrombolysis. (October 2019) - He, Xin-Wei; Shi, Yan-Hui; Liu, Yi-Sheng; Li, Ge-Fei; Zhao, Rong; Hu, Yue; Lin, Chang-Chun; Zhuang, Mei-Ting; Su, Jing-Jing; Liu, Jian-Ren
Abstract: Background and aims: Circulating microRNAs (miRNAs) have recently emerged as promising biomarkers for acute ischaemic stroke (AIS). However, the expression profiles of miRNAs in AIS patients receiving intravenous thrombolysis, and their associations with outcome have not been investigated. Methods: In a prospective cohort study, a total of 84 AIS patients, who received intravenous thrombolysis (21.4% received combined reperfusion therapy) and completed 3 month follow-up visits, were included. Favourable and unfavourable outcomes were defined as modified Rankin Scale (mRS) scores of 0–1 and 2–6, respectively. Plasma samples were collected at 24 h after thrombolysis. We used RNA sequencing to study miRNA profiles in 5 patients with unfavourable outcomes and 5 matched patients with favourable outcomes. Differentially expressed miRNAs were further validated in all cohorts using quantitative real-time polymerase chain reaction assays. Results: After identification and validation, we found that miR-124-3p, miR-125b-5p and miR-192-5p levels were higher in patients with unfavourable outcomes than in patients with favourable outcomes. Logistic regressions and receiver-operating characteristic curve analyses demonstrated that these altered miRNAs may function as predictive biomarkers for outcome in AIS patients receiving thrombolysis, whether combined with endovascular thrombectomy or not. In addition, miR-124-3p and miR-125b-5p were closely associated with stroke severity. Conclusions: A set of circulating microRNAs (miR-124-3p, miR-125b-5p and miR-192-5p) are associated with unfavourable 3 month outcomes and might have clinical utility in AIS patients receiving thrombolysis. Graphical abstract: Image 1 Highlights: Nineteen known microRNAs associated with outcome were discovered via RNA sequencing. Three microRNAs were validated using qRT-PCR and showed higher predictive efficiency. Two microRNAs were associated with stroke severity.